Correlation Between Lipid Profile Parameters and eGFR in Patients With Type 2 Diabetes - Alasbily, Hamza; Sana Abdalrahman,; Hayam Elawamy,; Fardous Fahmi,; Abeer Albarasi,; Adnan Asheibi,; Salim Ramadhan,; Ahmed Amhidi, (AlQalam Journal of Medical and Applied Sciences, 2025)
Dyslipidemia and chronic kidney disease (CKD) are common comorbidities in patients with type 2 diabetes (T2D), and accumulating evidence suggests a bidirectional relationship between lipid abnormalities and renal dysfunction. This study aimed to evaluate the association between serum lipid parameters and estimated glomerular filtration rate (eGFR) in T2D. A cross-sectional study was conducted at the Benghazi Diabetic Center between June and December 2024, including 280 adult with T2D. Demographic data (age, sex, and diabetes duration) and clinical parameters, including lipid profile, renal function tests, and glycated hemoglobin (HbA1c), were collected from patient records during follow-up. eGFR was calculated using the CKD-EPI 2021 equation and patients were categorized into six eGFR stages. Data were analyzed using SPSS version 27, and spearman's correlation test was used to determine the association between eGFR and lipid profile parameters. The mean age of participants was 58.4 ± 11.5 years, with a mean diabetes duration of 11.7 years and mean HbA1c of 7.8 ± 1.3%. Females comprised 55% of the cohort while males represent 45 %. The study also found the following mean values: creatinine 1.0 ± 0.9, urea 36.6 ± 24.3, GFR 83.1 ± 26.9, cholesterol 174.7 ± 45.3, triglyceride 165.4 ± 86.6, HDL 46.3 ± 12.4, LDL 86.6 ± 30.9, and VLDL 33.1 ± 17.3.Spearman's correlation revealed statistically significant weak negative correlations between eGFR and triglycerides (ρ = –0.206, P < 0.001), HDL (ρ = –0.198, P < 0.001), and TC (ρ = –0.158, P = 0.008) while low-density lipoprotein (LDL) exhibited a weak positive correlation with eGFR (ρ = 0.256, p < 0.001). These findings suggest a potential relationship between lipid abnormalities and renal function in T2D, emphasizing the importance of early lipid profile monitoring